(untitled) (Faridpur Medical College Journal, 2025)
Central serous chorioretinopathy is an eye condition that causes visual distortion, blurring, or decreased vision. It’s characterized by a serous fluid-filled detachment of the neurosensory retina in the macular area & often caused by leakage from the choroid, the layer of blood vessels beneath the retina. This study was carried out in a tertiary level referral center in Bangladesh, retrospectively evaluating patients who underwent focal laser for central serous chorioretinopathy to assess the visual and anatomical outcomes of focal laser photocoagulation for central serous chorioretinopathy and subsequent changes to central macular thickness and total volume in macular region. Baseline visual acuity, central macular thickness and total volume were recorded and calculated and compared with baseline and 4 weeks post focal laser. Data were compared using Wilcox signed-rank tests after using Shapiro-Wilk tests to determine normality. Total 25 eyes of 24 patients with central serous chorioretinopathy that underwent focal laser photocoagulation were included in this study. Patients were followed for a median of 1.5 months (range: 1.0–2.0 months) after treatment. Male and female ratio was 7:1. The visual acuity was significantly improved (0.55±0.24 to 0.87±0.21, p<0.001). The Mean Pre-laser central macular thickness was 475.24μm and the mean post-laser 177.08μm (475.24 ±196.52 μm to 177.08 ±52.55 μm, p<0.001), there was significant change. The change in total volume was significant statistically (10.3820 ±2.7169 mm3 to 7.6524 ± 0.7440 mm3, p<0.001). Of the 25 eyes, 4 had persistent sub-retinal fluid following laser, and of the 21 eyes with complete resolution of sub-retinal fluid, 2 developed recurrent sub-retinal fluid. Faridpur Med. Coll. J. 2025;20(1):24-28